2008
DOI: 10.23938/assn.0222
|View full text |Cite
|
Sign up to set email alerts
|

Patient satisfaction with the process of computerisation, consent and decision making during hospitalisation

Abstract: RESUMENLas organizaciones sanitarias han pasado de estar centradas en los profesionales a poner en el centro a los usuarios y sus expectativas. Las nuevas instituciones de salud quieren conocer la percepción de los pacientes sobre la calidad de la atención que reciben, en particular sobre la información recibida, el consentimiento y la toma de decisiones. Es necesario disponer de instrumentos de medida que exploren los distintos componentes del proceso de información, consentimiento y toma de decisiones.Fundam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…However, the research indicates that satisfaction with treatment results can be facilitated by evolving strategies to advance the self-unity, gaining and treating a patient's most important reason to experience treatment. In research, Simon et al (2007) confirmed that some key components should be considered when measuring patient satisfaction. Such as accurate knowledge of patients' rights and duties, the patient's family's participation so that he/she becomes aware of the level of medical services, as well as continuous communication with the patient after discharge from the hospital, the degree of understanding, assimilation of patient information and patient participation in processes of continuous improvement in the reality of healthcare services.…”
Section: Organisational Performancementioning
confidence: 84%
“…However, the research indicates that satisfaction with treatment results can be facilitated by evolving strategies to advance the self-unity, gaining and treating a patient's most important reason to experience treatment. In research, Simon et al (2007) confirmed that some key components should be considered when measuring patient satisfaction. Such as accurate knowledge of patients' rights and duties, the patient's family's participation so that he/she becomes aware of the level of medical services, as well as continuous communication with the patient after discharge from the hospital, the degree of understanding, assimilation of patient information and patient participation in processes of continuous improvement in the reality of healthcare services.…”
Section: Organisational Performancementioning
confidence: 84%